Analysis of Supporting Factors of Entrepreneurial Intention Mediated by the Courage to Take Risk in Gen Z Students in Tangerang - Jhonatan Leonard Kusuma; Tan, Pauline Henriette Pattyranie (Indonesian Marketing Journal, 2024)
Gen Z students have a deep understanding of market trends and also supporting factors that can be important capital in entrepreneurship. However, the many business ideas among students have not completely reduced the unemployment rate of graduates. This is a central issue in the development of the Indonesian economy because there is still fear in taking risks in entrepreneurship. This study aims to analyze the factors that influence the entrepreneurship intention of students in Tangerang, focusing on the influence of self-efficacy, family support, and institutional support, as well as the mediating role of the ability to take risks. The study used the Non-probability Sampling technique with the Purposive Sampling method, which involved respondents according to certain criteria. The results showed that family support and institutional support had a positive and significant influence on entrepreneurship intention. However, the ability to take risks did not have a significant influence on entrepreneurship intention. Mediation analysis showed that the ability to take risks significantly mediated the relationship between institutional support and self-efficacy with entrepreneurship intention, but not on family support. This study concludes that self-efficacy and support from family and institutions are important factors in increasing entrepreneurship intention, while the ability to take risks has a mediating role that varies depending on the type of support received by students.